Overhang structure and accuracy in laser engineered net shaping of Fe-Cr steel. (October 2018) - Wang, Xinlin; Deng, Dewei; Hu, Yingbin; Ning, Fuda; Wang, Hui; Cong, Weilong; Zhang, Hongchao
Highlights: The surface of overhang by reciprocating way was even and symmetrical. The z-increment had significant influences on the angle accuracy of overhang. The z-increment was proportional to (P/Qm) 1/4 (Qm/V). Abstract: Laser engineered net shaping (LENS), developed from laser cladding and rapid prototyping, has different promising applications such as aerospace, automotive, marine, tool manufacturing, etc. Due to the features of LENS process, the capability of overhang structure deposition was limited and some geometrical structures cannot be perfectly built. Investigating overhang building mechanisms and angle accuracy are crucial. In this study, the effects of scanning patterns (reciprocating and unidirectional deposition way) and vertical increment (z-increment) on overhang structures in LENS have been investigated. It was found that the overhang deposited in a reciprocating way exhibited higher geometry accuracy than that deposited in a unidirectional way. By optimizing z-increment, the discrepancy between the designed and experimental inclined angles of overhangs greatly decreased. The effects of processing parameters, including laser power, scanning speed, and powder feed rate, on the optimal z-increment were also investigated.